2022
DOI: 10.1111/sji.13216
|View full text |Cite
|
Sign up to set email alerts
|

A CD8+ T cell‐related genes prognostic model for hepatocellular carcinoma patients

Abstract: Immune checkpoint blockade (ICB) therapy is a promising treatment for hepatocellular carcinoma (HCC). However, it is limited by low response rates. Tumour‐infiltrating immune cells (TIICs), specifically CD8+ T cells, in the tumour microenvironment (TME) are related to tumour immune responses and are potential predictors for immunotherapeutic and survival outcomes. Therefore, we established a new CD8+ T cell‐related genes prognostic index (CD8T‐RGPI) for evaluating immune responses and prognostic outcomes for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Our study demonstrated that the high-CTD-2510F5.4 subgroup had higher TIDE scores and signi cantly lower ORR to ICI therapy compared to the low-CTD-2510F5.4 subgroup. The TIDE score is a reliable predictor of the response to ICI therapy(Fu et al 2020, Chang et al 2022). Furthermore, we observed that the high-CTD-2510F5.4 subgroup had higher IC50 values for sunitinib and dasatinib but lower IC50 values for cisplatin, doxorubicin, and rapamycin compared to the low-CTD-2510F5.4 subgroup.…”
mentioning
confidence: 99%
“…Our study demonstrated that the high-CTD-2510F5.4 subgroup had higher TIDE scores and signi cantly lower ORR to ICI therapy compared to the low-CTD-2510F5.4 subgroup. The TIDE score is a reliable predictor of the response to ICI therapy(Fu et al 2020, Chang et al 2022). Furthermore, we observed that the high-CTD-2510F5.4 subgroup had higher IC50 values for sunitinib and dasatinib but lower IC50 values for cisplatin, doxorubicin, and rapamycin compared to the low-CTD-2510F5.4 subgroup.…”
mentioning
confidence: 99%